2007
DOI: 10.1074/jbc.m600224200
|View full text |Cite
|
Sign up to set email alerts
|

αCP1 Mediates Stabilization of hTERT mRNA by Autocrine Human Growth Hormone

Abstract: We herein demonstrate that autocrine human growth hormone production in human mammary carcinoma cells results in increased telomerase activity as a result of specific up-regulation of telomerase catalytic subunit (human telomerase reverse transcriptase (hTERT)) mRNA and protein. This increase in hTERT gene expression is not due to increased transcriptional activation of the hTERT promoter but is the result of increased stability of hTERT mRNA exerted by CU-rich cis-regulatory sequences present in the 3-untrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…However, autocrine hGH increased mRNA levels of the breast cancer susceptibility gene, BRCA2, and the DNA repair protein involved in homologous recombination, X-ray repair cross complementing group-2 (XRCC2), in MDA-hGH cells compared with MDA-vec cells (Table 2). Consistent with our previous observations in MCF-7 cells (Emerald et al 2007), autocrine hGH also increased mRNA levels of TERT, the catalytic subunit of telomerase in MDA-MB-435S cells (Table 2). Functional antagonism of autocrine hGH reduces RL95-2 cell viability, total cell number, clonogenic survival and DNA damage after treatment with IR RL95-2 wild-type cells endogenously express and secrete hGH (Pandey et al 2008) and hence provide a suitable system for investigating the effect of functional antagonism of hGH on post-radiation cell survival.…”
Section: Autocrine Hgh Protects Mammary Carcinoma Cells Against Ir-insupporting
confidence: 80%
See 2 more Smart Citations
“…However, autocrine hGH increased mRNA levels of the breast cancer susceptibility gene, BRCA2, and the DNA repair protein involved in homologous recombination, X-ray repair cross complementing group-2 (XRCC2), in MDA-hGH cells compared with MDA-vec cells (Table 2). Consistent with our previous observations in MCF-7 cells (Emerald et al 2007), autocrine hGH also increased mRNA levels of TERT, the catalytic subunit of telomerase in MDA-MB-435S cells (Table 2). Functional antagonism of autocrine hGH reduces RL95-2 cell viability, total cell number, clonogenic survival and DNA damage after treatment with IR RL95-2 wild-type cells endogenously express and secrete hGH (Pandey et al 2008) and hence provide a suitable system for investigating the effect of functional antagonism of hGH on post-radiation cell survival.…”
Section: Autocrine Hgh Protects Mammary Carcinoma Cells Against Ir-insupporting
confidence: 80%
“…Another mechanism contributing to autocrine hGH-mediated radioresistance may be through the upregulation of telomerase (Emerald et al 2007). Autocrine hGH has been found to increase hTERT gene and protein expression, leading to an increase in telomerase activity in MCF-7 cells (Emerald et al 2007). Consistent with these studies we observed that autocrine hGH increased hTERT mRNA expression in MDA-MB-435S cells (Table 2).…”
Section: N M Bougen Et Al: Autocrine Human Gh Is Radioprotectivesupporting
confidence: 80%
See 1 more Smart Citation
“…Several studies have shown that CURE sequences function posttranscriptionally to regulate the mRNA stability of the CURE-containing mRNA (Levy et al, 1996;Czyzyk-Krzeska and Bendixen, 1999;Waggoner and Liebhaber, 2003;Wang et al, 2006;Emerald et al, 2007). To confirm that the CURE sequence in TP functions in its posttranscriptional regulation, we inserted three copies of wild-type and mutated TP CURE into the 3 0 -UTR of a firefly luciferase reporter gene, generating pMIR-CURE (CURE) and pMIRCUREmut (CUREmut), respectively ( Figure 2b; also see Supplementary materials and methods).…”
Section: Tp Is Strongly Induced In Serum-deprived Npc Cellsmentioning
confidence: 99%
“…Six micrograms of total RNA was used for cDNA synthesis with d(T) 20 primer (Omniscript RT, Qiagen, Tokyo, Japan). Quantitative PCR was performed for hTERT and b-actin cDNA with the primer set according to the report by Emerald et al (2007). Appropriate PCR cycle numbers were determined as 32 and 18 for hTERT and b-actin, respectively, at which the amount of all the PCR products were plotted within a linear range.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%